Social Value Orientation and Cooperation in Social Dilemmas: A Meta-Analysis - BALLIET, Daniel Patrick (Institutional Knowledge at Singapore Management University, 2009)
This article reports a meta-analysis of 82 studies assessing the relationship between social value orientation (SVO) and cooperation in social dilemmas. A significant and small to medium effect size was found (r =. 30). Results supported a hypothesis that the effect size was larger when participants were not paid (r =. 39) than when they were paid (r =. 23). The effect size was also larger in give-some (r =. 29) as opposed to take-some (r =. 22) games. However, contrary to expectations, the effect was not larger in one-shot, as opposed to iterated games. Findings are discussed in the context of theory on SVO and directions for future research are outlined.